THE RELATION BETWEEN RELIGION AND POLITICS IN MACHIAVELLI’S THOUGHT - Matić, Ivan (Serbian political thought, 2024)
The subject of this paper is the analysis of the unique position and role of religion in the political thought of Renaissance theorist Nicollo Machiavelli. In the first part of the paper, we will briefly discuss the general framework of his political thought, situating it in the period in which it was harshly criticized due to strong Christian cultural influence. The second part will examine Machiavelli’s understanding of religion, primarily based on its role in the development of the early Roman state. In the third part of the paper, we will compare Machiavelli’s positions on religion and the legitimacy of political actions within the context of their relation to the fundamental political and ethical elements of his thought.
Keywords: Machiavelli; religion; politics; morality; legitimacy; Renaissance; humanism